High Humidity Aerodynamic Effects Study on Offshore Wind Turbine Airfoil/Blade Performance through CFD Analysis - Weipeng Yue; Yu Xue; Yan Liu (International Journal of Rotating Machinery)
Damp air with high humidity combined with foggy, rainy weather, and icing in winter weather often is found to cause turbine performance degradation, and it is more concerned with offshore wind farm development. To address and understand the high humidity effects on wind turbine performance, our study has been conducted with spread sheet analysis on damp air properties investigation for air density and viscosity; then CFD modeling study using Fluent was carried out on airfoil and blade aerodynamic performance effects due to water vapor partial pressure of mixing flow and water condensation around leading edge and trailing edge of airfoil. It is found that the high humidity effects with water vapor mixing flow and water condensation thin film around airfoil may have insignificant effect directly on airfoil/blade performance; however, the indirect effects such as blade contamination and icing due to the water condensation may have significant effects on turbine performance degradation. Also it is that found the foggy weather with microwater droplet (including rainy weather) may cause higher drag that lead to turbine performance degradation. It is found that, at high temperature, the high humidity effect on air density cannot be ignored for annual energy production calculation. The blade contamination and icing phenomenon need to be further investigated in the next study.